Production of copper sulfate pentahydrate from copper cement - Azañero Ortiz, Ángel (2005)
In the south part of the country there oxidated copper minerals hard to leach and when you do it you get extracts are rich in copper but also contain polliting agents, that produces copper sulfate that does not match with the technical characteristics requiered for its industry use. This research consist in leaching the oxidated mineral, precipitation with iron, where the impuritis are eliminated, leaching of copper cement, and direct cristallization, out get a good product, technology can be applied to other similar mineral in Perú.